General practitioners practicing anesthesia care in rural Nepal – rewards and challenges - Dangal, Binod; Shah, Kashim; Dhungana, Rakshya; Neupane, Aayush (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Safe and accessible anesthetic care is critically limited in Asian countries. Perioperative anesthesia related complications are higher in resource limited countries. Neuraxial regional anesthesia is becoming popular and considered as anesthesia of choice in surgeries below umbilicus due to its safety, accessibility, efficacy and low cost. Due to limited numbers of anesthetists and anesthesia assistants, Medical Doctorate in General Practice (MPGP) are widely practicing different types of anesthetic care and performing varieties of surgeries in remote Nepal. Effective coordination, task sharing approach, clinical updates and specific training programs are required to strengthen anesthetic care of general practitioners in rural Nepal.